Drug-Induced Liver Toxicity - Stavrakeva K.; Popova M.; Esad M.; Apostolova E.; Kokova V.; Bacelova M.; Alakidi A.; Bivolarska A. (Acta Medica Bulgarica)
The liver performs many vital functions such as regulating homeostasis, bile production, storage of vitamins, and more. Another important function of the liver is to neutralize toxic substances entering the body. Substances entering the human body can be eliminated unchanged, retained unchanged, or undergo chemical transformation. Drugs are one of the most important and common causes of hepatotoxicity. It can manifest in various forms, ranging from elevated serum levels of transaminases to acute liver failure. The mechanisms of drug-induced liver damage may include the formation of a toxic metabolite (paracetamol), induction of oxidative stress, mitochondrial damage, suppression of key transcription factors and enzymes (methotrexate), suppression of beta-oxidation (valproate), impaired bile secretion and others. In some cases, hepatotoxicity is an idiosyncratic type and the exact mechanism of damage is unclear. Due to the importance of the problem, knowledge about the metabolism, potential adverse drug reactions, and the correct dosage regimen is essential.